How do we engage people in testing for COVID-19? A rapid qualitative evaluation of a testing programme in schools, GP surgeries and a university - Daniella Watson; Natalia Laverty Baralle; Jawahr Alagil; Krithika Anil; Sandy Ciccognani; Rachel Dewar-Haggart; Sarah Fearn; Julia Groot; Kathryn Knowles; Claire Meagher; Carmel McGrath; Sarah Muir; et al. (BMC, 2022)
Abstract Background The UK Scientific Advisory Group for Emergencies (SAGE) emphasises the need for high levels of engagement with communities and individuals to ensure the effectiveness of any COVID-19 testing programme. A novel pilot health surveillance programme to assess the feasibility of weekly community RT-LAMP (Reverse transcription loop-mediated isothermal amplification) testing for the SARS-CoV-2 virus using saliva samples collected at home was developed and piloted by the University of Southampton and Southampton City Council. Methods Rapid qualitative evaluation was conducted to explore experiences of those who took part in the programme, of those who declined and of those in the educational and healthcare organisations involved in the pilot testing who were responsible for roll-out. This included 77 interviews and 20 focus groups with 223 staff, students, pupils and household members from four schools, one university, and one community healthcare NHS trust. The insights generated and informed the design and modification of the Southampton COVID-19 Saliva Testing Programme and the next phase of community-testing. Results Discussions revealed that high levels of communication, trust and convenience were necessary to ensure people's engagement with the programme. Participants felt reassured by and pride in taking part in this novel programme. They suggested modifications to reduce the programme's environmental impact and overcome cultural barriers to participation. Conclusions Participants' and stakeholders' motivations, challenges and concerns need to be understood and these insights used to modify the programme in a continuous, real-time process to ensure and sustain engagement with testing over the extended period necessary. Community leaders and stakeholder organisations should be involved throughout programme development and implementation to optimise engagement.